The Perception of Fairness - An Important Principle Underpinning the Evaluation of Performance of R&D Scientists - Ranade, Shirish Anand; Kumar, Nikhil (Prabandhan: Indian Journal of Management, 2011)
Accomplishment of the goals by the institution is best reflected in the output of its employees and performance of the institution is thus reflected as a sum total of the achievements made by its employees and constituents. Performance appraisals are essentially an exercise in optimization and, therefore, are corrective and positive regulators to achieve the growth of individuals in consonance with that of the institution. A number of appraisal systems exist, but the perceived fairness or otherwise was the most important determinant of the applicability of these appraisal systems. The single most important factor or principle guiding the appraisals should be that a podium-finish metric is applicable only for competitions, where all things being equal, the best alone can win as in sports and athletics, but not in assessing scientific R&D work. Secondly, it is always the "deliverables" and only the "deliverables" that should count for the appraisal of performance. The assessment of the scientists in any institute should not be under the premise that perforce, there has to be a restriction in the number of scientists who can progress to the next higher grade. The performance appraisal should also be delivered to the scientists as a timely feedback about their performance to allow a mid-course correction, if so required. Performance appraisals, when perceived to be transparent and unbiased, truly allow an "equal opportunity" to each and every employee to exceed the performance benchmarks.